Ir(III)-Catalyzed Mild C-H Amidation of Arenes and Alkenes: An Efficient Usage of Acyl Azides as the Nitrogen Source - Ryu, Jaeyune; Kwak, Jaesung; Shin, Kwangmin; Lee, Donggun; Chang, Sukbok (AMER CHEMICAL SOC, 2013)
Reported herein is the development of the Ir(III)-catalyzed direct C-H amidation of arenes and alkenes using acyl azides as the nitrogen source. This procedure utilizes an in situ generated cationic half-sandwich iridium complex as a catalyst. The reaction takes place under very mild conditions, and a broad range of sp(2) C-H bonds of chelate group-containing arenes and olefins are smoothly amidated with acyl azides without the intervention of the Curtius rearrangement. Significantly, a wide range of reactants of aryl-, aliphatic-, and olefinic acyl azides were all efficiently amidated with high functional group tolerance. Using the developed approach, Z-enamides were readily accessed with a complete control of regio- and stereoselectivity. The developed direct amidation proceeds in the absence of external oxidants and releases molecular nitrogen as a single byproduct, thus offering an environmentally benign process with wide potential applications in organic synthesis and medicinal chemistry.
Keywords: PALLADIUM-CATALYZED AMIDATION; SANDWICH IRIDIUM COMPLEXES; CCK1 RECEPTOR ANTAGONISTS; BOND-FORMING REACTIONS; DIRECT AMINATION; STEREOSELECTIVE-SYNTHESIS; METAL-COMPLEXES; ORGANIC AZIDES; ARYL AZIDES; REGIOSELECTIVE-SYNTHESIS